The role of higher education in public sector education and training : the case of the School of Government, University of the Western Cape - Hamza, Enayatulla (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPA (Public Management and Planning))--University of Stellenbosch, 2010.